Typical symptoms included in the burnout syndrome - O. A. Ivashkina; M. K. Makeeva (Эндодонтия Today)
Aim. 1) Based on the survey conducted by us, to assess the prevalence of burnout among dentists of different specialties. 2) To determine the characteristic symptom complexes. 3) To study the effect of burnout on the professional activity of a dentist.Materials and Methods. With the help of a questionnaire compiled by us, a survey was conducted among 135 dentists of various specialties to identify the development of emotional burnout syndrome. Typical symptoms of burnout were evaluated and a symptom complex characteristic of the development of burnout was identified.Results. Among 135 respondents (40 men and 95 women), 55 of whom were dentists-therapists, 25-orthopedic dentists, 27 – orthodontists, 15–pediatric dentists, 5 dentists-surgeons, 8- universal dentists. All doctors reported the presence of symptoms such as: increased fatigue, drowsiness, mood changes, increased conflict; many noted the appearance of health problems: increased blood pressure, shortness of breath, frequent headaches and the presence of emotional symptoms: loneliness, sadness, disappointment in the profession, anxiety, cynicism. Which can be combined into symptom complexes characteristic of burnout: muscle symptoms, gastrointestinal symptoms, cardiovascular symptoms, respiratory symptoms, symptoms from the central nervous system, cardiovascular symptoms. The survey showed that pediatric dentists suffer from a large percentage of burnout (75%), followed by dental therapists (65%), general dentists (44%), dental surgeons (38%), orthopedic dentists (35%), dentists orthodontists (30%). Women are more prone to burnout (70%) than men. Dentists in the age range of 26-35 years are more likely to develop burnout (65.2%).Conclusions. The prevalence of the development of emotional burnout syndrome varies significantly depending on the narrow professional orientation of the specialist. Characteristic symptoms in the development of burnout were identified and isolated into symptom complexes.